Neuroprotective Effects of Salidroside on Cerebral Ischemia/Reperfusion-Induced Behavioral Impairment Involves the Dopaminergic System - Zhong, Zhi-feng; Han, Jing; Zhang, Ji-Zhou; Xiao, Qing; Chen, Jing-yan; Zhang, Kai; Hu, Juan; Chen, Li-dian (Frontiers in Pharmacology, 2019)
Salidroside, a phenylpropanoid glycoside, is the main bioactive component of Rhodiola rosea L. Salidroside has prominent anti-stroke effects in cerebral ischemia/reperfusion models. However, the underlying mechanisms of its actions are poorly understood. This study examined the anti-stroke effects of salidroside in middle cerebral artery occlusion (MCAO)-induced rat model of stroke and its potential mechanisms involving the dopaminergic system. Salidroside administration increased the levels of dopamine (DA), homovanillic acid (HVA), and 3,4-dihydroxyphenylacetic acid (DOPAC) in the ipsilateral striatum after induction of transient ischemia, which were assessed using microdialysis with high-performance liquid chromatography coupled with electrochemical detection (HPLC-ECD). Furthermore, treatment with salidroside ameliorated neurobehavioral impairment, assessed with the modified neurological severity scores (mNSS), the balance beam test, and the foot fault test. Moreover, enzyme-linked immunosorbent assay (ELISA) suggested that MCAO-induced reduction in monoamine oxidase (MAO) was inhibited by salidroside. Immunohistochemical and immunofluorescence analyses revealed high level of tyrosine hydroxylase (TH) in the ipsilateral striatal caudate putamen (CPu) after cerebral ischemia/reperfusion, which could be further elevated by salidroside. In addition, salidroside could reverse the decreased immunoreactivity of TH in the substantia nigra pars compacta (SNpc). These results suggest that the anti-stroke effects of salidroside in MCAO-induced cerebral ischemia/reperfusion may involve the modulation of monoamine metabolism in the striatum and SNpc, which may be related to the function of the dopaminergic system in the rat brain.